2021
DOI: 10.1038/s41598-021-02548-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological associations with genomic variation in SARS-CoV-2

Abstract: SARS-CoV-2 (CoV) is the etiological agent of the COVID-19 pandemic and evolves to evade both host immune systems and intervention strategies. We divided the CoV genome into 29 constituent regions and applied novel analytical approaches to identify associations between CoV genomic features and epidemiological metadata. Our results show that nonstructural protein 3 (nsp3) and Spike protein (S) have the highest variation and greatest correlation with the viral whole-genome variation. S protein variation is correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Such as mutation P314L at Nsp12 was reported to decrease the protein stability. 27 , 45 , 61 , 134 , 158 163
Fig. 4 Heatmap of the mutation site and the mutational impact of SARS-CoV-2 variants on the non-structural proteins.
…”
Section: Molecular Characteristics Of Sequence and The Encoded Protei...mentioning
confidence: 99%
“…Such as mutation P314L at Nsp12 was reported to decrease the protein stability. 27 , 45 , 61 , 134 , 158 163
Fig. 4 Heatmap of the mutation site and the mutational impact of SARS-CoV-2 variants on the non-structural proteins.
…”
Section: Molecular Characteristics Of Sequence and The Encoded Protei...mentioning
confidence: 99%
“…We previously have shown that SARS-CoV-2 genomic variation is independent of host characteristics (e.g., age and gender) 7 . SARS-CoV-2 genome variation over time has introduced new strains with various functional characteristics such as a set of mutations in spike protein, the primary vaccine antigen 8 , and folding conformations in the virus variants and related functions 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It was highlighted that some geographic regions (populations) have unusually high (many new variants) while others have low (isolated) viral phylogenetic diversity. Such studies provided a direction to prioritize genes associated with outcome predictors (e.g., health, therapeutic, and vaccine outcomes) and to improve DNA tests for predicting disease status [ 13 ]. Current study is aimed at identifying SARS-CoV-2 variants and mutation profile in the coronavirus genome presented during the second wave of coronavirus pandemic in Uzbekistan and assessing their impact on the disease severity.…”
Section: Introductionmentioning
confidence: 99%